PENGARUH LAYANAN DIGITAL MARKETING BERBASIS MOBILE APPS DAN E-SERVICE QUALITY TERHADAP TINGKAT KEPUASAN YANG BERDAMPAK PADA LOYALITAS PELANGGAN - Rediyono; Putera, Muhammad Tommy Fimi (Jurnal Manajemen, 2024)
The increasingly rapid development of technology provides quite significant changes in various spheres of life, including the economic and business sectors. One form of implication is the use of a digital marketing service strategy based on mobile apps and e-service quality which is oriented towards the level of customer satisfaction and loyalty. This research was\conducted using descriptive methods through a qualitative approach. The data used in this research is secondary data in the form of theoretical basis and empirical findings from previous research obtained through literature study. The conclusion that can be drawn from this research is that the application of digital marketing and e-service quality has a positive and significant effect on the level of customer satisfaction. Customer satisfaction is proven to have an influence on customer loyalty to make repeat purchases of a product or service.